Pelatihan Digital Marketing Dalam Upaya Meningkatkan Penghasilan Ibu Rumah Tangga Majlis Taklim Perempuan Kecamatan Jatiyoso - Prima Prihatini (Yayasan Literasi Sains Indonesia, 2022)
The development of technology is growing very rapidly, so that people like it or not have to follow the development of this technology, otherwise they will be left behind. The use of social media is the most powerful marketing tool because people from different backgrounds are very active in using it. With social media, business actors can interact widely with various groups, with cheap and suitable ones to market their products, so that what is offered has a great opportunity to be sold. The main problem faced by housewives is the lack of knowledge in marketing both conventionally (offline) and online, especially e-commerce. The lack of knowledge of housewives about digital marketing has inspired the community service team to deliver socialization and provide training on the use of this information and communication technology. If housewives understand the importance of digital marketing for business opportunities, they are expected to be motivated to use digital marketing as a means of communication and business opportunities for their business, and can practice it directly by utilizing social media. Based on the main problems of partners, namely the lack of marketing management information, the solution offered to partners is to provide material related to digital marketing, offline marketing to increase revenue. The method used is lecture, question and answer, and simulation. The target to be achieved in community service activities is the implementation of the introduction of digital marketing in an effort to increase the income of housewives in order to become a prosperous family. The program's output targets are scientific articles published through the journal ISSN, and increased empowerment of housewives and the ability to take advantage of marketing opportunities through online and offline media.